TYPES OF CHILDREN WITH DISABILITIES AND THEIR INVOLVEMENT IN INCLUSIVE EDUCATION - Mamatisayeva Surayyo Ahmadjon qizi (Galaxy International Interdisciplinary Research Journal, 2021)
The task of modern continuing education is to improve the quality of education and upbringing, to ensure a high scientific level of thorough teaching of the basics of science. This task involves the development of students' knowledge of the sciences through the improvement of teaching methods, as well as the intensive formation of skills to effectively apply the acquired knowledge in practice. Inclusive education (derived from English, inclusive, inclusion, adaptation, inclusion, inclusion) to overcome barriers (discrimination) between children with disabilities and healthy, children with special needs, (for some reason, disabilities) adolescents or an education system that represents inclusion in the general education process aimed at adapting to social life regardless of economic difficulties.